The Mayor of a Municipality – Competences, Qualifications, Current Status in the Slovak Republic - Kováčová, Eleonóra (Przegląd Politologiczny, 2018)
The mandatory authorities – the municipal office and the mayor of the municipality – play an irreplaceable role at the municipal level. Both bodies are elected. These authorities influence the direction of municipal development in the upcoming term of office, the municipal representatives’ protection of citizens’ needs and interests as well as fulfilment of the tasks and obligations imposed by the law. The main aim of the article is to clarify the importance and seriousness of the mayor as the highest representative of the municipal government in the Slovak Republic. Another aim is to present new realities connected with the mayor’s office as well as new requirements associated with it.